"Hallelujah": Parody, Political Catharsis, and Grieving the 2016 Election with Saturday Night Live. Issue 2 (15th March 2018) - Davisson, Amber
Abstract : In the aftermath of a bitter election, Kate McKinnon opened the November 12th episode of Saturday Night Live dressed as Hillary Clinton and singing Leonard Cohen's classic, "Hallelujah." The performance rhetorically employs the hidden polemic of parody to intertwine the affective responses to Cohen's death and the 2016 election, thereby creating a political catharsis. McKinnon's parody, which eschewed the traditionally rational rhetoric associated with the political sphere in favor of a pathetic appeal, capitalized on the kairotic moment to affectively move the public through grief to a place of action.